In vitro and preclinical assessment of an intranasal spray formulation of parathyroid hormone PTH 1-34 for the treatment of osteoporosis - Williams, Allan J.; Jordan, Faron; King, Gareth; Lewis, Andrew L.; Illum, Lisbeth; Masud, Tahir; Perkins, Alan C.; Pearson, Richard G. (Elsevier, 2017)
Osteoporosis treatment with PTH 1-34 injections significantly reduces the incidence of bone fracture. Potential further reductions in fracture rate should be observed through nasal spray delivery to address the poor compliance associated with patient dislike of repeated PTH 1-34 subcutaneous injections. In vitro human osteoblast-like Saos-2 cell intracellular cAMP levels were used to define PTH 1-34 nasal spray formulation bioactivity. The chemically synthesised PTH 1-34 had an EC50 of 0.76nM. Absorption enhancers polyethylene glycol (15)-hydroxystearate (Solutol® HS15), poloxamer 407, chitosan or sodium hyaluronate did not diminish the bioactivity of PTH 1-34 within an in vitro cell culture model (p>0.05). We also demonstrated the effectiveness of the transmucosal absorption enhancer Solutol® HS15 in a nasal spray formulation using a preclinical pharmacokinetic model. In Sprague-Dawley rats without the absorption enhancer the uptake of PTH 1-34 into the blood via intranasal delivery produced a Cmax of 2.1±0.5 ng/ml compared to 13.7±1.6 ng/ml with Solutol® HS15 enhancer (p=0.016) and a Cmax14.8±8 ng/ml in subcutaneous injections. Together these data illustrate that the nasal spray formulation bioactivity in vitro is not affected by the nasal spray absorption enhancers investigated, and the Solutol® HS15 nasal spray formulation had an equivalent pharmacokinetic profile to subcutaneous injection in the rat model. The Solutol® HS15 formulation therefore demonstrated potential as a PTH 1-34 nasal spray formulation for the treatment of osteoporosis.